2015
DOI: 10.5100/jje.51.s398
|View full text |Cite
|
Sign up to set email alerts
|

1C1-3 The Effect of Carrying a Military Backpack on a Transverse Slope and Sand Surface on Lower Limb Kinetics

Abstract: The objective of this study was to understand gait kinetics while walking on a sand surface (vs. hard surface) with wearing a traditional military ALICE backpack (vs. modularized MOLLE backpack). Twenty healthy male students participated in this study. Each participant completed a total of 72 trials (3 good trials for each testing configuration). These testing conditions were combinations of two surface types (hard, sand), two transverse slopes (flat, 10°), two walking speeds (self-selected, 4 km/h), and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…The observed reduction in peak anterior GRF amplitudes during the push off phase while walking on sand may be representative of foot and ankle instability due to impairment of the midtarsal locking mechanism in the late stance phase which provides an adequate lever to push off against. It has previously been reported that walking on stable ground compared with walking on sand results in a greater maximal braking force and maximal propulsive force in healthy male students aged 18–30 years [29]. Of note, we did not find any significant main effects of “surface” for peak medio-lateral GRFs.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The observed reduction in peak anterior GRF amplitudes during the push off phase while walking on sand may be representative of foot and ankle instability due to impairment of the midtarsal locking mechanism in the late stance phase which provides an adequate lever to push off against. It has previously been reported that walking on stable ground compared with walking on sand results in a greater maximal braking force and maximal propulsive force in healthy male students aged 18–30 years [29]. Of note, we did not find any significant main effects of “surface” for peak medio-lateral GRFs.…”
Section: Discussioncontrasting
confidence: 54%
“…The alignment tabs ensured that all shear forces were transmitted to the surface of the force plate. Previous studies confirmed that this force plate construction embedded into the walkway is well-suited to reduce dissipation of force and to accurately identify forces while walking on the two surface conditions [29–32]. Test-retest reliability was assessed for GRF and EMG data and revealed intra-class correlation coefficients (ICC) > 0.6 and 0.53, respectively.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…The alignment tabs ensured all shear forces were transmitted to the surface of the force plate. Previous studies confirmed that this force plate isolation technique could serve well to reduce the dissipation of force and accurately identify measured GRF on ballast and sand [5,8].…”
Section: Experimental Set-upmentioning
confidence: 81%
“…Lejeune et al investigated the mechanics and energetics of human locomotion on sand [4]. The studies performed by Kim and Yoo analyzed upper and lower limb biomechanics when carrying a military backpack while walking on cross-slope sand surfaces [5,6]. Other studies have focused on the effects of walking on gravel, like railroad ballast.…”
Section: Introductionmentioning
confidence: 99%